Hypodematium chrysolepis comb. nov. from Africa and H. eglandulosum sp. nov. from Asia (Hypodematiaceae) - Fan, Xue-Ping; Lu, Ngan Thi; Zhang, Liang; Zhang, Li-Bing (Phytotaxa, 2021)
A new fern species, Hypodematium eglandulosum, is described and illustrated from southern China and Southeast Asia, and a new combination is made, H. chrysolepis, from Africa. Hypodematium eglandulosum is distinguished from its similar species by plants eglandular, leaves 3-pinnatifid, and stipes upward sparsely covered with acicular hairs or nearly glabrous. The description and photographs of H. eglandulosum are provided. Aspidium chrysolepis is currently treated as a synonym of H. crenatum, but it should be recognized.